Neurodydaktyczne aspekty procesu rozwiązywania testowego zadania matematycznego na podstawie badań eyetrackingowych - ROŻEK, Bożena; BŁASIAK, Władysław; ANDRZEJEWSKA, Magdalena; GODLEWSKA, Małgorzata; KOZUBOWSKI, Paweł; ROSIEK, Roman; SAJKA, Mirosława; STOLIŃSKA, Anna; WCISŁO, Dariusz (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
Contemporarily the necessity of regarding the knowledge of brain structure and functions in the didactic processes is more and more frequently discussed. Neurodidactics, as a cross-disciplinary science is engaged in the learning and education process which is based on the results of research on brain functioning. One of the non-invasive methods that can provide us with knowledge on brain functioning is the research carried out with an eye-tracker, a device used for tracing eyeball movements of a tested person. This paper will present a part of the research in which the eye-tracking technology has been used. The aim of the presented research was an attempt to analyse the depth of information processing by a pupil during solving a mathematical test task. The research results point to certain characteristic pupils’ behaviour while making decision concerning the choice of an answer marked by them.